(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
Asthma remains the most prevalent chronic condition in childhood. In recent years, substantial progress has been made in characterizing the microbial communities of the upper and lower airways, clarifying their relevance to pediatric asthma. Early investigations confirmed that both upper and lower airways harbor complex microbiomes and that disturbances in these communities are associated with pediatric asthma. Evidence suggests that the airway microbiome in infancy may predict subsequent asthma development and is modifiable by environmental exposures, including respiratory viral infections. Moreover, airway microbial composition has been linked to asthma severity, disease control, and frequency of exacerbations. Advances in multi-omics technologies have enabled deeper exploration of interactions between airway microbes and host immune responses in children with asthma. Current research increasingly focuses on translating these findings into preventive and therapeutic strategies. The airway microbiome represents a promising avenue for improving understanding of pediatric asthma, with implications for diagnosis, prognosis, and potential treatment approaches. Further studies are required to confirm these associations and integrate microbiome-based insights into clinical practice.